Analysis of monetary policy response during normal period and during covid-19 pandemic to inflation in Indonesia - Nefi Sukma; Fery Andrianus (Institute of Computer Science (IOCS), 2023)
The purpose of this study is to analyze the effect of Money Supply, Interest Rates and Exchange Rates on Inflation during the Covid-19 pandemic and see the differences in monetary policy responses during normal times and during the Covid-19 pandemic in Indonesia.The method used in this study is Markov Switching Autoregressive by Hamilton which is a model of combining Markov and Autoregressive chains that can explain structural changes in time series data. The variables used in this study are Inflation as the dependent variable and Jub, Interest Rates, and Exchange Rates as independent variables, and are processed using RStudio 4.2.1 and Eviews 10 software. The results show that in regime 1, Jub, Interest Rate, and Exchange Rate have no significant influence on Inflation. While in regime 2, Jub, Interest Rate, and Exchange Rate have a significant influence on Inflation. The response of monetary policy during normal times to the development of macroeconomic conditions, especially at the level of inflation, Jub, interest rates, and the rupiah exchange rate is that Bank Indonesia is aware of the risks that will occur in the macroeconomic balance in Indonesia by ensuring adequate liquidity, maintaining monetary and financial system stabilization so that stimulus in the economy can run effectively. Meanwhile, during the crisis period including the Covid-19 pandemic, Bank Indonesia has coordinated very closely with the Financial Services Authority (OJK) and also with the Government to formulate policies to mitigate the impact of the Covid-19 pandemic so that macroeconomic and financial system stability is well maintained to maintain the momentum of Indonesia's economic growth